Depressive symptoms and mortality - effect variation by body mass index: a prospective study in a primary care population - Rantanen Ansa T; Kautiainen Hannu; Korhonen Päivi E (SPRINGERNATURE, 2025)
Background/objective: Pre-existing diseases have been found to affect the relationship between body mass index (BMI) and mortality. However, psychiatric disorders common in general population have not been previously addressed. The aim of this study was to assess the relationship of depressive symptoms and BMI with all-cause mortality.
Methods: A prospective cohort study in Finnish primary care setting was conducted. A population survey identified 3072 middle-aged subjects who had elevated cardiovascular risk. Subjects who attended clinical examination and completed Beck's Depression Inventory (BDI) (n = 2509) were included in this analysis. Effect of depressive symptoms and BMI on all-cause mortality after 14 years follow-up was estimated in models adjusted for age, sex, education years, current smoking, alcohol use, physical activity, total cholesterol, systolic blood pressure, and glucose disorders.
Results: When subjects with and without increased depressive symptoms were compared, the fully adjusted hazard ratios (HR) for all-cause mortality in the BMI categories (<25.0, 25.0-29.9, 30.0-34.9, ≥35.0 kg/m2) were 3.26 (95% CI 1.83 to 5.82), 1.31 (95% CI 0.83 to 2.06), 1.27 (95% CI 0.76 to 2.11), and 1.25 (95% CI 0.63 to 2.48), respectively. The lowest risk of death was among non-depressive subjects who had BMI < 25.0 kg/m2.
Conclusions: Effect of increased depressive symptoms on all-cause mortality risk seems to vary with BMI. Elevated mortality risk is especially apparent among depressive subjects with normal weight. Among individuals with overweight and obesity, increased depressive symptoms seem not to further increase all-cause mortality.